Pengaruh Brand Image Dan Brand Trust Terhadap Loyalitas Pelanggan Pada Produk Apple Iphone - Deninda Putri Ardita; Yusi Faizathul Octavia; Rosyia Wardani (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This study aims to examine the effect of brand image and brand trust on customer loyalty to apple iphone products (a case study on STIE AMM Mataram students). So that the research variables consist of three (3) independent variables, namely brand image (X1), brand trust (X2), and the dependent variable, namely customer loyalty (Y). The aims of this research are (1) to find out whether brand image has a significant effect on customer loyalty, (2) to find out whether brand trust has a significant effect on customer loyalty, (3) to find out whether brand image and brand trust have a simultaneous effect on customer loyalty. In this study, 2 types of research were used, namely qualitative and quantitative with a total population and sample of 60 students from STIE AMM Mataram. The data collection technique used in this study is a statement in the form of a questionnaire. The results showed that: (1) brand image has a positive and significant effect on customer loyalty because tcount > ttable, namely 1,842 > 2,002, (2) brand trust has a positive and significant effect on customer loyalty because tcount > ttable, namely 7,078 > 2,002. Fcount has a greater value than f table, namely the Fcount value is 66,021 with a sig = 0,000.